The Robot and Us An 'Antidisciplinary' Perspective on the Scientific and Social Impacts of Robotics - Carrozza, Maria Chiara; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers a clear, yet comprehensive overview of the role of robots in our society. It especially focuses on the interaction between humans and robots, and on the social and political aspects of the integration of robots with humans, in their everyday life, both in the private and working sphere alike. Based on the lessons held by the author at "Scuola di Politiche" (transl. School of Political Sciences), this self-contained book mainly addresses an educated, though not-specialist, audience. .
Are we going through a real revolution -- On the way to robotics -- The socialization of robotics -- Our friend the robot -- The robot inside us.
Keywords: Engineering; Control engineering; Robotics; Automation; Biotechnology; User interfaces (Computer systems).; Human-computer interaction; Artificial intelligence; Technology and Engineering; Control, Robotics, Automation; Biotechnology; User Interfaces and Human Computer Interaction; Artificial Intelligence